Kepastian Hukum Perkawinan bagi Transeksual yang Melakukan Penyesuaian Alat Kelamin - Pradayani, Santi; Qoyyima, Azrotul; Rato, Dominikus; Ohoiwutun, Y.A. Triana (University of Merdeka Malang, 2024)
The dynamics of genital reconstruction create disparities in the rights of transsexual individuals to form families and the legitimacy of marriage in Indonesia for transsexual individuals who lack clarity under the Marriage Law. The methodology employed is normative legal research, analyzing applicable regulations and religious perspectives. The discussion encompasses an explanation of the position of transsexual individuals following gender reassignment surgery, which impacts the legitimacy of marriage for transsexual individuals who have undergone genital reconstruction, in accordance with religious law and the Marriage Law, as well as the legal implications of the marriages conducted. The analysis indicates that the six officially recognized religions in Indonesia tend to reject the legitimacy of transsexual marriages, viewing them as same-sex unions that violate religious norms. The legal implications for transsexual individuals vary: for those without medical indications, marriages are considered same-sex; whereas for those who undergo surgery to affirm their gender, marriages may be deemed valid. The conclusion reveals a dissonance between legal frameworks and social norms, as well as challenges faced by transsexual individuals in accessing equal marriage rights.